Wood handbook : wood as an engineering material. (U.S. Dept. of Agriculture, Forest Service, Forest Products Laboratory, 1999)
This handbook is intended as an aid to more efficient use of wood as a construction material. It provides engineers, architects, and others with a source of information on the physical and mechanical properties of wood and how these properties are affected by variations in wood.
Title from title page of source document.
Also available in online version from Forest Products Laboratory.
Keywords: Wood.; Wood -- Handbooks, manuals, etc.; Wood -- Research.; elektronické knihy; electronic books